OPTN/SRTR 2017 Annual Data Report: Kidney - Hart, A.; Smith, J. M.; Skeans, M. A.; Gustafson, S. K.; Wilk, A. R.; Castro, S.; Robinson, A.; Wainright, J. L.; Snyder, J. J.; Kasiske, B. L.; Israni, A. K. (American journal of transplantation, 2019)
Many positive trends in kidney transplantation were notable in 2017. Deceased donor kidney transplant rates and counts continued to rise, the kidney transplant waiting list declined for the third year in a row after decades of growth, and both short‐ and long‐term allograft survival continued to improve year over year. In total, more than 220,000 patients were living in the United States with a functioning allograft. With 3 years of data available since implementation of the new kidney allocation system, better prediction of longer‐term results of the allocation policy changes became possible. The data also reveal several areas in need of improvement and attention. Overall, the challenge of providing adequate access to kidney transplant persisted nationally, with additional dramatic regional variation. The proportion of living donor kidney transplants in both adults and children continued to fall, and racial disparities in living donor kidney transplant grew in the past decade.